Envisioning emerging frontiers on human gut microbiota and its applications. Issue 1 (24th September 2020) - Ventura, Marco; Milani, Christian; Turroni, Francesca; van Sinderen, Douwe
Summary: The human gut microbiota is involved in multiple health‐influencing host interactions during the host's entire life span. Microbes colonize the infant gut instantaneously after birth and subsequently the founding and interactive progress of this early gut microbiota is considered to be driven and modulated by different host‐ and microbe‐associated forces. A rising number of studies propose that the composition of the human gut microbiota in the early stages of life impact on the human health conditions at later stages of life. This notion has powered research aimed at detailed investigations of the infant gut microbiota composition. Nevertheless, the molecular mechanisms supporting the gut microbiome functionality and the interaction of the early gut microbes with the human host remain largely unknown. Abstract : This manuscript provides a general overview about the future avenues of research in the field of microbiota.